The effectiveness of acceptance and commitment therapy on emotional processing in female students with social anxiety disorder - Daryaye Lal, Gholamreza; Akbari, Bahman (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effectiveness of acceptance and commitment therapy on emotional processes in girls with social anxiety disorder. Methods: The present study was a quasi-experimental study with a pretest-posttest design and follow-up with a control group. The statistical population of the present study included all 26 to 18 years old female undergraduate students of Guilan University (11271 people) in the academic year 1397-98. At this stage, the Social Panic Questionnaire (SPIN) of Connor et al. (2000) was administered to all undergraduate female students of Guilan University who were selected using random sampling method. Acceptance and commitment therapy sessions for social anxiety disorder (Hayes, 2004) were conducted in 10 2-hour group sessions, but the control group remained on the waiting list. Analysis of variance with repeated measures and SPSS software were used to analyze the data. Results: The results showed that acceptance and commitment therapy on the improvement of repression (F=10.80, P=0.003), unpleasant emotional experience (F=12.86, P